Norfloxacin removal by ultraviolet-activated sodium percarbonate and sodium hypochlorite: process optimization and anion effect - Guvenc, Senem Yazici; Turk, Oruc Kaan; Can-Guven, Emine; Garazade, Narmin; Varank, Gamze (IWA PUBLISHING, 2023)
The efficiency of UV-activated sodium percarbonate (SPC) and sodium hypochlorite (SHC) in Norfloxacin (Norf) removal from an aqueous solution was assessed. Control experiments were conducted and the synergistic effect of the UV-SHC and UV-SPC processes were 0.61 and 2.89, respectively. According to the first-order reaction rate constants, the process rates were ranked as UV-SPC > SPC > UV and UV-SHC > SHC > UV. Central composite design was applied to determine the optimum operating conditions for maximum Norf removal. Under optimum conditions (UV-SPC: 1 mg/L initial Norf, 4 mM SPC, pH 3, 50 min; UV-SHC: 1 mg/L initial Norf, 1 mM SHC, pH 7, 8 min), the removal yields for the UV-SPC and UV-SHC were 71.8 and 72.1%, respectively. HCO3-, Cl-, NO3-, and SO42- negatively affected both processes. UV-SPC and UV-SHC processes were effective for Norf removal from aqueous solution. Similar removal efficiencies were obtained with both processes; however, this removal efficiency was achieved in a much shorter time and more economically with the UV-SHC process.
Keywords: advanced oxidation; antibiotic removal; sodium hypochlorite; sodium percarbonate; water matrix effect; WASTE-WATER TREATMENT; HYDROGEN-PEROXIDE; COMMUNITY STRUCTURE; AQUEOUS-SOLUTION; FENTON PROCESS; DEGRADATION; PERSULFATE; CIPROFLOXACIN; WASTEWATERS; Engineering; Environmental Sciences & Ecology; Water Resources